(untitled) (Our Nature, 2025)
In recent years, human-leopard conflict has become a significant issue in the Gulmi district. This study aims to explore the current situation of such conflicts by conducting field visits from August 2019 to January 2020 and documenting data from the past five years through questionnaires. A total of 743 livestock were reported as victims of leopard attacks. There was a significant positive correlation between the frequency of livestock incidents and the number of losses (r = 0.907, p = 0.574 at a significance level of 0.05). The gender of the livestock also showed a positive correlation with incident frequency (r = 0.972). Most incidents involved free-grazing livestock, with the highest occurrence in August (11.27%). A strong relationship was found between people’s responses to leopard activities and the distance of their residence from the forest (χ² = 39.97, df = 6, p < 0.05). Additionally, there was a significant association between the level of education and people’s responses to leopard behavior (χ² = 13.69, df = 9, p < 0.05). The most conflicting areas were marginal zones between forests and private farmlands, with most encounters occurring at night. Affected individuals expressed dissatisfaction with the government’s compensation scheme. To mitigate human-leopard conflicts, it is recommended that livestock be reared in controlled environments, and that forest entry by people be limited to low-risk times.